2017
DOI: 10.1097/jpa.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physician Assistant Faculty Intent to Leave Academia

Abstract: The intent of PA faculty to leave academia and return to clinical practice can be meaningfully predicted by 5 items. Importantly, these items are in the purview of institutional administrators and can be used to target PA faculty retention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…Based on our results, burnout is always a factor for CDs intent to leave their position, their program, or academia. Similar observations have been noted in prior studies in the intent to leave and burnout, as well as a relationship between depression, burnout, and professional outcomes among clinically practicing PAs [9][10][11][12][13][14][15]. In our analyses, very few other faculty indicated an intention to leave their position, despite 43% also reporting moderate-high levels of burn out.…”
Section: Faculty Considering Leaving Their Positionsupporting
confidence: 89%
“…Based on our results, burnout is always a factor for CDs intent to leave their position, their program, or academia. Similar observations have been noted in prior studies in the intent to leave and burnout, as well as a relationship between depression, burnout, and professional outcomes among clinically practicing PAs [9][10][11][12][13][14][15]. In our analyses, very few other faculty indicated an intention to leave their position, despite 43% also reporting moderate-high levels of burn out.…”
Section: Faculty Considering Leaving Their Positionsupporting
confidence: 89%
“…By 2017, the average number of peer-reviewed publications per PA faculty had fallen to 2.74, and the median number of publications for PA faculty was zero. 3 At that time, a little over 50% of PA faculty had never produced a single publication in their entire career. 4 Scarcity of PA faculty scholarly publications can have significant consequences.…”
Section: Introductionmentioning
confidence: 99%
“…3 Prior factors associated with PA faculty intent to leave education include inadequate organizational support, which is naturally exacerbated when there is an insufficient number of faculty. 12,13 A study conducted prior to the pandemic showed that among general internal medicine physician, PA, and nurse practitioner faculty, high stress levels were present in 67%, with 38% meeting the criteria for burnout. 11 Factors associated with burnout included low control over workload and lack of support staff.…”
Section: Discussionmentioning
confidence: 99%